Differential antibiosis against helicoverpa armigera exerted by distinct inhibitory repeat domains of capsicum annuum proteinase inhibitors - Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Phytochemistry, 2014)
Plant defensive serine proteinase inhibitors (Pis) are known to have negative impact on digestive physiology of herbivore insects and thus have a crucial role in plant protection. Here, we have assessed the efficacy and specificity of three previously characterized inhibitory repeat domain (IRD) variants from Capsicum annuum PIs viz., IRD-7, -9 and -12 against gut proteinases from Helicoverpa armigera. Comparative study of in silico binding energy revealed that IRD-9 possesses higher affinity towards H. armigera serine proteinases as compared to IRD-7 and -12. H. armigera fed on artificial diet containing 5 TIU/g of recombinant IRD proteins exhibited differential effects on larval growth, survival rate and other nutritional parameters. Major digestive gut trypsin and chymotrypsin genes were down regulated in the IRD fed larvae, while few of them were up-regulated, this indicate alterations in insect digestive physiology. The results corroborated with proteinase activity assays and zymography. These findings suggest that the sequence variations among Pis reflect in their efficacy against proteinases in vitro and in vivo, which also could be used for developing tailor-made multi-domain inhibitor gene(s). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Capsicum annuum; Helicoverpa armigera; Inhibitory repeat domain; Proteases; Proteinase inhibitors